Performance evaluation of solar pv inverter controls for overvoltage mitigation in mv distribution networks - Almeida D.; Pasupuleti J.; Raveendran S.K.; Basir Khan M.R. (MDPI AG, 2023)
The incorporation of real and reactive power control of solar photovoltaic (PV) inverters has received significant interest as an onsite countermeasure to the voltage rise problem. This paper presents a comprehensive analysis of the involvement of active power curtailment and reactive power absorption techniques of solar PV inverters for voltage regulation in medium voltage (MV) distribution networks. A case study has been conducted for a generic MV distribution network in Malaysia, demonstrating the effectiveness of fixed power factor control, VoltVar, and VoltWatt controls in mitigating overvoltage issues that have arisen due to the extensive integration of solar PV systems. The results revealed that the incorporation of real and reactive power controls of solar PV inverters aids in successfully mitigating overvoltage issues and support network operating conditions. Furthermore, the comparative analysis demonstrated the importance of employing the most appropriate control technique for improved network performance. 2021 by the authors. Licensee MDPI, Basel, Switzerland.